1982
DOI: 10.2307/2130294
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Training and Productivity: A Look at who Publishes

Abstract: In two recent studies, Morgan and Fitzgerald and Robey ranked American political science departments on the basis of their faculty's research productivity in the major political science journals. The rankings which they produced were at some variance with the reputational rankings reported by Somit and Tanenhaus, Cartter, and, more recently, Ladd and Lipset. In particular, Robey reports that "… some southern universities seem to have made great strides in the last ten years while some Ivy League schools do not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…An extensive bibliography on the topic is available from the authors upon request. ell 1998;Garand and Graddy 1999;McCormick and Bernick 1982;McCormick and Rice 2001;Miller, Tien, and Peebler 1996).…”
Section: N O T E Smentioning
confidence: 99%
“…An extensive bibliography on the topic is available from the authors upon request. ell 1998;Garand and Graddy 1999;McCormick and Bernick 1982;McCormick and Rice 2001;Miller, Tien, and Peebler 1996).…”
Section: N O T E Smentioning
confidence: 99%
“…23 In other cases restricted journal sets have been defined as a select number of supposedly 'reputable' journals. 24 Neither of these approaches is entirely satisfactory; they are either arbitrary or subjective and do not guarantee that the restricted journal sets consist of the journals of the highest possible quality. To optimize the choice of journals for the research described below, the restricted set was defined as the European journals of politics with the highest mean citations per published article, otherwise known as citation impact.…”
Section: Restricted Journal Setmentioning
confidence: 99%
“…It was applied initially to university departments of psychology 18 but has also been applied to university departments of politics. 19 Its use in Britain has been limited to two studies of university psychology departments. 20 The research reported in this article represents a modest attempt to extend the technique to British university departments of politics.…”
mentioning
confidence: 99%
“…One of the central responsibilities of a doctoral program is to train students to do high-quality original research, and the best way to determine the extent to which programs succeed in this endeavor is to measure the productivity of their graduates. McCormick and Bernick (1982) Both of these studies were well received, but both were criticized for concentrating on journal publications at the exclusion of books. Many scholars felt, perhaps rightly, that schools differed in their research philosophies, with some stressing journal publications and others emphasizing books.…”
mentioning
confidence: 99%